2013
DOI: 10.7150/ijms.5272
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Associates with Small Vessel Disease More Closely Than Large Vessel Disease

Abstract: Background: Hyperhomocysteinemia was believed to be an independent risk factor for stroke and associate with small vessel disease (SVD) related stroke and large vessel disease (LVD) related stroke differently. However it's still unclear which type of stroke associated with homocysteine (HCY) more strongly because the conclusions of previous studies were contradictory. In this study we focused on the subclinical angiopathies of stroke, i.e., SVD and LVD instead of stroke subtypes and sought to compare the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
0
30
0
3
Order By: Relevance
“…Although it did not reduce cognitive decline in the same study, this may be because cognitive testing has been shown to be insensitive to detect changes over a 2‐ to 3‐year period in this cerebral small vessel disease . Furthermore, several case‐control studies have shown that elevated tHcy levels are a stronger risk factor for SVS than other ischemic stroke subtypes and that tHcy levels are higher in patients with cerebral small vessel disease than in healthy controls, although such studies only show associations and cannot exclude confounding.…”
mentioning
confidence: 86%
“…Although it did not reduce cognitive decline in the same study, this may be because cognitive testing has been shown to be insensitive to detect changes over a 2‐ to 3‐year period in this cerebral small vessel disease . Furthermore, several case‐control studies have shown that elevated tHcy levels are a stronger risk factor for SVS than other ischemic stroke subtypes and that tHcy levels are higher in patients with cerebral small vessel disease than in healthy controls, although such studies only show associations and cannot exclude confounding.…”
mentioning
confidence: 86%
“…Hyperhomocysteinemia (Hcy level ≥15.90 µmol/l) was more common in patients with large-vessel atherosclerotic stroke and CE stroke in the Turkish population [60]. By contrast, a study found that Hcy level was associated with SVDrelated stroke more strongly than LVD-related stroke [61]. Hyperhomocysteinemia was an independent risk factor for SVD [62].…”
Section: Metabolism-related Markersmentioning
confidence: 99%
“…Excess production of Hcy can occur as a result of impaired metabolism due to a deficiency in cofactors (vitamin B6, B12, folate) or to genetic alteration in metabolic enzymes (methionine synthase [MS], methyltetrahydrofolate reductase [MTHFR], cystathionine‐ β ‐synthase [CBS], and cystathionine‐ γ ‐lyase). HHcy is commonly seen in about 5 to 12% of the general population and is recognized as a risk factor for cerebrovascular diseases (Clarke, ; Feng et al., ; Okura et al., ), diabetes, obesity, and hepatic steatosis (Dara et al., ; Ji and Kaplowitz, ). Various epidemiological and longitudinal studies suggested a causal link between Hcy and cognitive impairment (Nurk et al., ).…”
mentioning
confidence: 99%